Risk of Complicated Birth at Term in Nulliparous and Multiparous Women Using Routinely Collected Maternity Data in England: Cohort Study. Issue 3 (25th September 2021) - Jardine, J.; Blotkamp, A.; Gurol-Urganci, I.; Knight, H.; Harris, T.; Hawdon, J.; van der Meulen, J.; Walker, K.; Pasupathy, D.
Abstract : ( BMJ . 2020;371:1–10) Risk assessment during antenatal and intrapartum care allows health care providers to identify patients who might have complications during childbirth. In the UK, risk factors such as woman's age, body mass index (BMI), and the presence of specific clinical and obstetric conditions are used to identify in which location a woman should deliver. The National Institute for Health and Care Excellence (NICE) guidelines state while low-risk women could deliver at home or in a midwife setting, women with increased risk are recommended to deliver in an obstetric unit. The primary aim of this study was to assess the NICE guidelines to determine the rate of complicated at-term birth in low-risk women and to assess if risk classification can be improved by expanding the list of considered risk factors including parity.